RENCANA STRATEGIS DINAS KOPERASI DAN USAHA MIKRO DALAM MENINGKATKAN KUALITAS SDM PELAKU UMKM KABUPATEN NGAWI - fatqu roiz; Umayatul Khumairo' (Fakultas Ekonomi Bisnis Islam, 2022)
The owner of Micro, Small, and Medium Enterprise (called: UMKM) need an increased quality of human resource with the goal can growing up the enterprise, because many enterprises are hard to rival. Training from department cooperation and Micro, Small, and Medium Enterprise and assisting the owner of Micro, Small, and Medium Enterprises to be competent and made creativity and new innovations. This article uses qualitative research methods with methods taking data from the field of interviews, documentation, and observation. department cooperation and Micro, Small, and Medium Enterprise's many strategies to the owner of Micro, Small, and Medium Enterprise have a high quality of human resources to compete with else. Human resources are one of the success keys from got the goal. Strategy from department cooperation and Micro, Small and Medium Enterprise to the owner of Micro, Small and Medium is training to create a numbered certificate of allowance home industries production (called:PIRT) for an enterprise, giving a legal certificate to the owner enterprise and training a make a viral snack to the owner of Micro, Small and Medium